RESIDENTS’ COMPLIANCE WITH BUILDING SETBACKS IN IBADAN NORTH LOCAL GOVERNMENT AREA OF OYO STATE, NIGERIA - ADEJUMO, S. A.; FATIMAH O. BADIRU (International Studies Journal)
Housing standards violation in cities of Nigeria is worrisome particularly in urban centers where activities of planning authority should be effective. The nexus between the socioeconomic characteristics of residents and the desire to violate the standards despite their inherent benefits is yet to be unraveled. This study, therefore, examines the residents’ compliance with housing setback standards in Ibadan North Local Government Area, Oyo State. The cross sectional research design was used. Both primary and secondary information were sourced.  A total of 327 copies of pretested questionnaire were administered to residents of Ibadan North Local Government Area, especially building owners in three randomly selected communities representing high, medium and low residential densities. Issues that were investigated include, the extent of compliance to the building setback and the rate of conversion of the setbacks to other uses. Findings revealed that majority of residents who complied with setbacks standard were males (55.6%), Yoruba (84.9%) and graduates (62.5%). The sum of 30.3% and 34.9%, respectively, complied to the rear and front view setbacks of their buildings.  More than half of the residents (50.8%) did not comply with 30meters setback between septic soak away and well/borehole location. The majority of the setbacks that were converted to other uses in low residential areas was used for security post (81.6%) while the largest proportion (35.4%) in medium and high-density areas (15.7%) were used for shop construction. Among all socioeconomic variables considered, the contribution of education (χ2=19.650) to the residents’ level of compliance with building setback was the highest. There was no association between income (r=-0.273) and the level of compliance with setback standards in the study area. Therefore, the study suggests community-based public enlightenment on the benefits of adherence to housing standards by the planning authority while the authority should be equipped for effective monitoring and development control.